Self-assembled hyaluronic acid nanoparticles for osteoarthritis treatment - Kang, Li Jung; Yoon, Juhwan; Rho, Jun Gi; Han, Hwa Seung; Lee, Seulbi; Oh, Young Soo; Kim, Hwan; Kim, Eunha; Kim, Seok Jung; Lim, Yong Taik; Park, Jae Hyung; Song, Woo Keun; et al. (Biomaterials, 2021)
Although osteoarthritis (OA) is the most prevalent degenerative joint disease, there is no effective disease-modifying therapy. We report an empty self-assembled hyaluronic acid nanoparticle (HA-NP) as a potential therapeutic agent for OA treatment. In mouse primary articular chondrocytes, HA-NPs blocked the receptor-mediated cellular uptake of free low-molecular-weight HA, and the cellular uptake of HA-NPs increased by ectopic expression of CD44, using an adenoviral delivery system (Ad-Cd44). HA-NP showed in vitro resistance to digestion with hyaluronidase and in vivo long-term retention ability in knee joint, compared with free high-molecular-weight (HMW) HA. CD44 expression increased in the damaged articular cartilage of patients and mice with OA. Ad-Cd44 infection and IL-1β treatment induced in vitro phenotypes of OA by enhancing catabolic gene expression in primary articular chondrocytes, and these effects were attenuated by HA-NP, but not HMW HA. Both Cd44 deficiency and intra-articular injection of HA-NP protected joint cartilage against OA development in the OA mouse model. NF-κB was found to mediate CD44-induced catabolic factor expression and HA-NP inhibited CD44-induced NF-κB activation in chondrocytes. Our results identify an empty HA-NP as a potential therapeutic agent targeting CD44 for OA treatment, and the CD44-NF-κB-catabolic gene axis as an underlying mechanism of destructive cartilage disorders.
Keywords: Articular chondrocytes; Catabolic factors; Catabolic genes; Cd44; Cellular uptake; High molecular weight; In-vitro; Osteoarthritis; Self assembled nanoparticles; Therapeutic agents; Animals; Cartilage, Articular; Chondrocytes; Humans; Hyaluronic Acid; Mice; Nanoparticles; Osteoarthritis; Catabolic factor; CD44; Hyaluronic acid; Osteoarthritis; Self-assembled nanoparticle